Do the angle and length of the eustachian tube influence the development of chronic otitis media?. (16th March 2015) - Dinç, Aykut Erdem; Damar, Murat; Uğur, Mehmet Birol; Öz, Ibrahim Ilker; Eliçora, Sultan Şevik; Bişkin, Sultan; Tutar, Hakan
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To compare the eustachian tube (ET) angle (ETa) and length (ETl) of ears with and without chronic otitis media (COM), and to determine the relationship between ET anatomy and the development of COM. Study Design A retrospective case‐control study. Methods The study group comprised 125 patients (age range, 8–79 years; 64 males and 61 females) with 124 normal ears and 126 diseased ears, including ears with chronic suppurative otitis media (CSOM) with central perforation, intratympanic tympanosclerosis (ITTS), cholesteatoma, and a tympanic membrane with retraction pockets (TMRP). ET angle and length were measured using computed tomography employing the multiplanar reconstruction technique. Results The ETa was significantly more horizontal in diseased versus normal ears of all study groups (P = .030), and there was no group difference in ETl (P = .160). ETl was shorter in CSOM versus ITTS ears and normal ears (P = .007 and P = .003, respectively) and in cholesteatoma versus TMRP ears (P = .014). In the unilateral COM group, there were no significant differences in the ETa or ETl of diseased versus contralateral normal ears (P = .155 and P = .710, respectively). The ETa was significantly more horizontal in childhood‐onset diseased versus normal ears (P = .027), and there was no group difference in ETl (P = .732). The ETa (P = .002) and ETl (P < .001) were significantly greater in males than females. Conclusions A more horizontal ETa and shorter ETl could be contributory (though not significantly) etiological factors in the development of COM. Level of Evidence 3b Laryngoscope, 125:2187–2192, 2015